2018
DOI: 10.1038/s41388-018-0325-x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MAOA in epithelia inhibits adenocarcinoma development, cell proliferation and cancer stem cells in prostate

Abstract: Monoamine oxidase A (MAOA) is a mitochondrial enzyme, which degrades monoamine neurotransmitters and dietary amines and produces HO. Recent studies have shown increased MAOA expression in prostate cancer (PCa), glioma, and classical Hodgkin lymphoma. However, the biological function of MAOA in cancer development remains unknown. In this study, we investigated the role of MAOA in the development of prostate adenocarcinoma by creating a prostate-specific Pten/MAOA knockout (KO) mouse model, in which MAOA-floxP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…According to the study of Du et al, MAOA mediates a signaling pathway contributing to reactive oxygen species generation, through which cancer‐associated fibroblasts induce the epithelial‐mesenchymal transition, metastasis, and infiltration of prostate cancer 40 . Liao etal demonstrated that MAOA promoted prostate tumor cell proliferation by mediating AKT phosphorylation and that MAOA absence hampered the progression of prostate cancer 41 . In the present study, we found that decreased MAOA in HCC correlated with poor survival outcome.…”
Section: Discussionsupporting
confidence: 61%
“…According to the study of Du et al, MAOA mediates a signaling pathway contributing to reactive oxygen species generation, through which cancer‐associated fibroblasts induce the epithelial‐mesenchymal transition, metastasis, and infiltration of prostate cancer 40 . Liao etal demonstrated that MAOA promoted prostate tumor cell proliferation by mediating AKT phosphorylation and that MAOA absence hampered the progression of prostate cancer 41 . In the present study, we found that decreased MAOA in HCC correlated with poor survival outcome.…”
Section: Discussionsupporting
confidence: 61%
“…MAOA is a mitochondrial enzyme that degrades monoamine neurotransmitters and dietary amines and produces hydrogen peroxide. It has a well-established role in promoting aggressive prostate cancer cell growth, invasion, and metastasis [3437]. MAOA is also reported as an AR target gene with an androgen response element (ARE) in its promoter [38].…”
Section: Resultsmentioning
confidence: 99%
“…MAOB and MAOA have dramatic influence in the etiology of many neurological diseases . Moreover, Liao et al have proved that MAOA was involved in the development of adenocarcinoma. Prior study performed by Hussain et al and Tong et al elucidated the vital functions of MAOB on Alzheimer's disease and Parkinson's disease, but its function in some types of cancers such as endometrial carcinoma still remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Growing reports disclosed that miR-522 is nor- MAOB and MAOA have dramatic influence in the etiology of many neurological diseases. 18,19 Moreover, Liao et al 30 have proved that MAOA was involved in the development of adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%